Incidence of Pneumonia among Stroke Patient in Zainoel Abidin Hospital Banda Aceh – A Descriptive Study - Sofia, Rosa Emelda; Musadir, Nasrul; Danial, Dini Raaikhani (Jurnal Ilmiah Kesehatan, 2024)
Background: Stroke is an acute and focal neurological deficit syndrome resulting from vascular injury (infarction, bleeding) in the central nervous system. Apart from that, stroke causes the second number of deaths in the world with the highest morbidity and the incidence increases in young and middle age (<55 y.o). In 2018, the prevalence of stroke in Aceh was 13.389 people. On the other hand, pneumonia is the most common non-neurological complication in the acute phase of stroke. In severe brain injury, it causes sympathetic overactivity which causes Systemic Inflammatory Response Syndrome (SIRS). The aim of the research is to provide a descriptive overview of the incidence of pneumonia in stroke patient including gender, onset, stroke classification, complications/comorbidities, use of antibiotics and length of treatment. Method: Quantitative research type with a descriptive design with a cross-sectional study and purposive sampling approach. The population is medical records of stroke patients who experienced pneumonia during the treatment period for the period January-December 2023 and samples were taken in the Medical Records Room at RSUD dr. Zainoel Abidin Banda Aceh. Results: This study showed that the dominant age of SAP was over 55 years and 60 cases of ischemic stroke (77.9%) and 17 cases (22.1%) of hemorrhagic stroke was male patient. The highest stroke onset is 1-7 days. The main comorbid factors were hypertension and diabetes mellitus. The use of antibiotics was 3rd generation cephalosporins. Conclusion: the incidence of pneumonia in stroke sufferers was influenced by age, gender and comorbid factors.